(untitled) (Communications in Computational Physics, 2014)
This study aims to investigate turbulent plasma flow using the lattice Boltzmann (LB) method. A double population model D2Q9-D2Q4 is employed to calculate the plasma velocity and temperature fields. Along with the calculation process a conversion procedure is made between the LB and the physical unit systems, so that thermo-physical properties variation is fully accounted for and the convergence is checked in physical space. The configuration domain and the boundary condition treatment are selected based on the most cited studies in order to illustrate a realistic situation. The jet morphology analysis gives credible results by comparison with commonly published works. It was demonstrated also that accounting for the substrate as wall boundary condition modify greatly the flow and temperature structures with may affect absolutely the particles behavior during its in-flight in the hot gas.